2021
DOI: 10.3389/fimmu.2021.812210
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Low-Dose Radiotherapy to Modulate the Tumor Microenvironment of Liver Metastases

Abstract: Despite multiple therapeutic approaches, the presence of liver metastases carries a guarded prognosis, urgently necessitating further clinical and scientific research to develop curative interventions. The liver is an immunoprivileged organ that suppresses the effectiveness of immunotherapies in patients with hepatic metastases. Cancer immunotherapies have been successfully bolstered by low-dose radiotherapy (LDRT), which is capable of reprogramming the tumor microenvironment (TME) from an immunosuppressive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Low-dose XRT created an early window of low intratumoral pressure 1 to 3 days after XRT. A recent study showed that low-dose XRT modulates the tumor stroma and downregulates cancer-associated fibroblasts, 30 which causes the stroma to become more permeable and allows for effector immune cells (mainly natural killer and T cells) to infiltrate the TME. Once the natural killer and T cells infiltrate the stroma, immune-mediated killing begins.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose XRT created an early window of low intratumoral pressure 1 to 3 days after XRT. A recent study showed that low-dose XRT modulates the tumor stroma and downregulates cancer-associated fibroblasts, 30 which causes the stroma to become more permeable and allows for effector immune cells (mainly natural killer and T cells) to infiltrate the TME. Once the natural killer and T cells infiltrate the stroma, immune-mediated killing begins.…”
Section: Discussionmentioning
confidence: 99%
“…HDRT negatively affects the tumor immune microenvironment by damaging the tumor vasculature [ 69 , 70 , 71 ] and reducing blood flow, which preclude immune cell infiltration and exacerbates the hypoxia-driven immunosuppressive environment [ 58 , 72 , 73 ]. In contrast, LDRT promotes immune effector cell infiltration, acting as a ‘TME modulator’ [ 18 ]. Dovedi et al demonstrated that low-dose fractionated radiotherapy (5*2 Gy) enhanced T-cell trafficking to irradiated tumor sites and augmented resident anticancer T-cell responses with the capacity to mediate the abscopal effect [ 74 ].…”
Section: Immunobiology Mechanisms Of Hdrt + Ldrtmentioning
confidence: 99%
“…Interestingly, HDRT’s and LDRT’s effects on anti-tumor immunity seem to be complementary in many pathways. In contrast to HDRT, LDRT plays a critical role in modulating the tumor immune microenvironment via enhancing immune effector cell infiltration and attenuating the immune-suppressive effects of RT [ 18 ]. Thus, using a ‘hybrid’ RT regimen may be the way to optimally stimulate anti-tumor immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that low-dose radiotherapy (LDRT), i.e., lower than 2 Gy/fraction, can effectively reprogram the stroma from an immunosuppressive to immunostimulatory and synergize with immunotherapy ( 35 37 ). Interestingly, the mechanisms by which HDRT and LDRT regulate the antitumor immune system appear to be complementary ( 38 ). Therefore, the use of the multimodal radiotherapy regimen, such as HDRT and LDRT, can achieve optimal antitumor effects.…”
Section: Introductionmentioning
confidence: 99%